EICHHORNIA CRASSIPES: A HYDROPHYTE REMOVES CHROMIUM IN INDUSTRIAL WASTEWATERS. A ECO-FRIENDLY PHYTOREMEDIAL PLANT SOURCES - T. SHEHNAZ BEGUM; M. VIJAYAKAKSHMI; M.DEECARAMAN; K.ANBARASU (International Journal of Pharma and Bio Sciences, 2016)
Chromium is one of the environmental pollutant that is toxic even at low concentration. Industrial waste water discharge is the most important source of chromium in water. Phytoremediation an emerging technology for contaminated soils, ground water and waste water that is low cost and environmental friendly have been employed in this study. Water hyacinth (Eichhornia crassipes) has been used to remediate the industrial waste water. In the present study, Eichhornia crassipes has been tested for removal of chromium from aqueous chromium solution. Young plants of equal size were cultured in a plastic tub containing a synthetic solution of chromium (K2Cr2O7). Eichhornia crassipes was cultured in tap water which was supplemented with three different concentrations 10, 25 and 50 mg/L of chromium for 10 and 20 days. The digested samples were analyzed using AAS (Atomic Absorption Spectrophotometer). The plant performed extremely well in removing the chromium at low concentration. Addition of chromium at lower concentration (10mg/L) was found harmless and the absorption of chromium was found to be higher upto 20 days, but at 25 and 50 mg/L of chromium, the plants have shown morphological symptoms of toxicity. The present study conducted in this regard revealed the efficiency of Eichhornia crassipes in removing chromium from industrial waste waters.